Effect of different phyto additive mixtures on colostrum production, health status, blood indices and hormonal profile of Black Bengal goats at first kidding - SINGH, AMIT KUMAR; Champak Bhakat56@gmail.com; Bed Singh; Muthupalani Karunakaran; Tapas Kumar Dutta (Indian Journal of Dairy Science, 2025)
This study was conducted to investigate the effects of different phyto additive mixture on colostrum production, health status, blood indices and hormonal profile of Black Bengal goats at first kidding. 21 Black Bengal goat (BBG) kids of similar age and body weight were divided equally into three comparable groups viz. Control (No supplementation), T1 and T2 in this study. Two different powders of phyto additive mixtures comprising equal amounts of PAM-1: Curcuma longa & Allium sativum and PAM-2: Curcuma longa & Ocimum sanctum were prepared and supplemented to T1 (PAM-1 @15g/Kg DM conc.) and T2 (PAM-2 @15g/Kg DM conc.) for a period of 10 months. Significant improvement (P<0.001) in colostrum yield was observed in T1 and T2 groups than control group without affecting (P>0.05) colostrum composition, udder health (pH, EC, MCMT, SCC) and relative immunity of goats at first kidding. There was significant reduction (P<0.001) in age at first kidding in T1 and T2 groups than control group. Significantly improved (P<0.001) body weight and BCS at kidding was obtained in T1 and T2 groups than control group. NEFA levels at kidding was lower (P<0.001) in T1 and T2 groups than control group goats. Blood enzymes (ALT, AST, ALP), haematology (RBC, WBC, Hb, PCV, HCR) and biochemical parameters (Glucose, Total urea, Total protein) remained unchained (P>0.05). However, a significant reduction in (P<0.001) blood lipids (total lipids, total cholesterol, triglycerides) were observed. There was higher level (P<0.001) of Prolactin and T4 hormones in T1 and T2 groups than control group goats. Whereas, levels of Cortisol and T3 were lower (P<0.001) in T1 and T2 than control group goats. Based on findings of this study, it can be concluded that supplementation of phyto additive mixtures (PAM-1 and PAM-2) containing equal amounts of Curcuma longa & Allium sativum and Curcuma longa & Ocimum sanctum @15g/Kg DM conc. for 10 months in Black Bengal goats may improve colostrum production, health status and hormonal profile without affecting blood haematology and biochemistry at first kidding.